The Visualization of Spirits in The Digital World as Creative Commodities in Indonesia - Sujatmiko, Guguh (ULTIMART Jurnal Komunikasi Visual, 2023)
This study analyzes the visualization process of spirits in the supernatural world that are seen by humans in the physical world through digital contents as creative commodities. Spirit content is still promising as a creative commodity in Indonesia. This content has a lot of curious fans because it can be facilitated visually. The content, which is believed to have different worlds, is able to unite the physical world and the energy world. The energy world includes the digital world and the supernatural world. Thus, the differences between the worlds are interesting to analyze for creative process development. This study uses the qualitative method, the virtual theory from Rob Shield used to map the position of spirits, humans, and platforms. The communication theory is used to see the visual transfer process to society, and Sasmita explores the signs that appear in the content. The findings indicate that representing intangible entities through locally relevant visual symbols proved beneficial for content creators, enabling the production of innovative content that enhances audience interaction. This was achieved by conveying messages to the audience through the construction of symbols and leveraging visual perception. Keywords: creative commodities; digital world; spirits content; visual process.